Design and development of high frequency high power transformer for renewable energy application - Abd Rahim, Abd Razak; Soib, Taib; Ismail, Daut (Universiti Sains Malaysia (USM), 2008)
Organized by Universiti Sains Malaysia (USM), 20th - 22th July 2005 at Penang, Malaysia.